ORGANIZATIONAL FACTORS AND TURNOVER INTENTION: THE MEDIATING ROLE OF COMMITMENT - Muhamad Fajar Pratama; Justine Tanuwijaya; B Medina Nilasari (INSTITUT TEKNOLOGI DAN BISNIS PGRI DEWANTARA JOMBANG, 2026)
This study investigates the mediating role of organizational commitment in the relationships of organizational culture, transformational leadership, and job resources with turnover intention among local employees in a multinational electronics manufacturing company in Cibitung, Indonesia. A quantitative explanatory design was employed using survey data from 262 employees selected through probability sampling. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling with AMOS. The findings show that job resources significantly reduce turnover intention and strengthen organizational commitment. Organizational culture and transformational leadership do not have significant direct effects on turnover intention, while transformational leadership also does not significantly predict organizational commitment. Organizational culture significantly affects organizational commitment, but in a negative direction. Unexpectedly, organizational commitment shows a significant positive association with turnover intention, contrary to mainstream theory. Mediation analysis further indicates that organizational commitment significantly mediates the effect of organizational culture on turnover intention, but does not mediate the effects of transformational leadership or job resources. These findings suggest that, in multinational manufacturing settings, organizational commitment may not uniformly serve as a retention mechanism and should be understood as contingent on the form of commitment and the organizational conditions experienced by employees.